The Influence of School Principal Supervision and School Climate on Teacher Performance in MTSN Parak Laweh Padang - Azvi Rahmi; Susi Yuliastanty; Handriadi; Rifma (Fakultas Ilmu Pendidikan UNP)
Based on field observations, it is observed that teachers' performance at MTsNParakLaweh Padang is still low. Researchers suspect that supervision of school principals and school climate affects teacher performance in MTsNParakLaweh Padang, therefore a research is conducted to test the truth. This study aims to reveal the influence of school principal supervision and school climate on teacher performance at MTsNParakLaweh Padang. The hypothesis proposed in this study are: 1) If supervision of principal high, hence giving high influence to teacher performance; 2) If the high school climate, then give a high influence on teacher performance; 3) If the principal's supervision and high school climate, then give a high influence collectively on the performance of teachers. This research was conducted by using correlational quantitative method. The population of this research is all teachers of MTsNParakLaweh Padang. The sample of this research is taken by using Stratified Proportional Random Sampling technique. Samples obtained 54 people. Data were collected by questionnaire with Likert scale that has been tested for validity and reliability. Data were analyzed by correlation and regression technique.The result of data analysis shows that: 1) supervisor of principal has an effect on teacher performance 11,4%, 2) school climate influence to teacher performance equal to 5.1% and 3) supervision of headmaster and school climate together influence to teacher performance equal to 15.2%. Based on the descriptive analysis revealed that the principal's supervision and school climate are equally influential to improve teacher performance.